The Effectiveness of Sharia Audit in Islamic Financial Institution - Ayu, Sandra Ayu; Maisya Pratiwi; Aryuna, Wemi (EKONOMIKA SYARIAH : Journal of Economic Studies, 2024)
Sharia audit in Islamic financial institutions plays an important role in ensuring that operations, products, and services offered are in accordance with sharia principles to maintain the integrity, transparency, and accountability of the institution. However, sharia auditors face various challenges in conducting sharia audits, such as technical issues, lack of management support, and the absence of comprehensive sharia auditing standards.  This qualitative research aims to describe the effectiveness of sharia audit implementation by analyzing the audit framework and audit work papers at Bank Nagari Syariah Business Unit through a phenomenological approach, with data collected through in-depth interviews with bank leaders. The results showed that the implemented sharia audit framework includes the structure of the sharia supervision organization, the scope of the audit, to reporting and follow-up. Sharia audits are proven to increase customer confidence as they provide assurance that the bank's products and services have undergone strict supervision in accordance with sharia principles. Ongoing monitoring from OJK and regular audits by external auditors help maintain audit quality and effectiveness, creating a robust compliance system that contributes to the stability, accountability and reputation of banks in the Islamic finance industry. Audit syariah pada lembaga keuangan syariah berperan penting dalam memastikan operasional, produk, dan layanan yang ditawarkan sesuai dengan prinsip-prinsip syariah untuk menjaga integritas, transparansi, dan akuntabilitas lembaga. Namun, auditor syariah menghadapi bermacam tantangan dalam pelaksanaan audit syariah, seperti permasalahan teknis, kurangnya dukungan manajemen, dan belum adanya standar audit syariah yang komprehensif. Penelitian kualitatif ini bertujuan mendeskripsikan efektivitas pelaksanaan audit syariah dengan menganalisis kerangka kerja audit dan kertas kerja audit di Bank Nagari Unit Usaha Syariah melalui pendekatan fenomenologis, dengan data yang dikumpulkan melalui wawancara mendalam kepada pimpinan bank. Hasil penelitian menunjukkan bahwa kerangka kerja audit syariah yang diterapkan mencakup struktur organisasi pengawasan syariah, ruang lingkup audit, hingga pelaporan dan tindak lanjut. Audit syariah terbukti meningkatkan kepercayaan nasabah karena memberikan jaminan bahwa produk dan layanan bank telah melalui pengawasan ketat sesuai prinsip syariah. Pemantauan berkelanjutan dari OJK dan audit rutin oleh auditor eksternal turut menjaga kualitas dan efektivitas audit, menciptakan sistem kepatuhan kokoh yang berkontribusi pada stabilitas, akuntabilitas, dan reputasi bank dalam industri keuangan syariah.